Monitoring and evaluation of the cytotoxicity, uptake flux and phenotypic profile of marine microalga tetraselmis gracilis during cu (ii) exposure in controlled laboratory condition - SUCHETA SADHU; R. KIRUBAGARAN (International Journal of Pharma and Bio Sciences, 2017)
Marine ecosystem naturally contains copper. It is an essential metal ion in phytoplankton physiology though oligodynamic in nature. Copper enters into the food chain through cellular uptake by aquatic organisms, for instance microalgae, which belongs to the phytoplankton community and serve as primary producer in a food chain. To understand the mechanism of toxicity of Cu (II) with marine microalga, Tetraselmis gracilis as a model organism was investigated through growth rate inhibition bioassays for a period of 96 h along with control. During the study phenotypic responses of T. gracilis were explored at different concentrations of Cu (II). The evaluation revealed dose dependent significant decline in the phenotypic profile of T. gracilis along the time profile. Further, micrometric assay, FTIR assay, SEM photomicrograph assay substantiated the role of Cu (II) in damaging cell membrane, alteration in growth profile, etc. The results were tested through one-way ANOVA and considered significant at p < 0.05.